Establishment of a localized acute implant-associated Staphylococcus aureus bone infection model in sheep. Issue 6 (14th June 2021) - Klein, Karina; Schweizer, Tiziano A; Siwy, Katharina; Lechmann, Beat; Karol, Agnieszka; von Rechenberg, Brigitte; Achermann, Yvonne; Darwiche, Salim E
Abstract: Orthopedic implant-associated bacterial infections with Staphylococcus aureus constitute a major clinical problem, and large pre-clinical animal models remain scarce. The aim of this study was to establish a standardized method of a localized, acute S. aureus bone infection in the presence of complex implanted devices in a sheep model. Four sheep underwent surgery receiving a complex implanted metallic device with a component stabilizing a bone defect created in the left tibial metaphysis, and an attached component placed in adjacent soft tissue. The bone defect was inoculated with S. aureus strain ATCC25293 (1 × 10 4 CFU). Twenty one days later, the surgery site was macroscopically evaluated, tissue samples and implants harvested for bacterial cell count quantification and tissue samples histologically analyzed. The animals exhibited clinical signs of localized infection (e.g. swelling, lameness, pain) but did not develop symptoms of sepsis. After euthanasia, macroscopic assessment revealed a localized bone and soft tissue infection at the surgery site. Histologically, an acute inflammation with neutrophils but also signs of bone destruction with necrosis was noted. An ovine model of a localized, acute S. aureus bone infection with complex implants was successfully established and could be used to test novel treatments against orthopedic implant-associated infections. Abstract : Implant-associated Staphylococcus aureus infection model in sheep.